The Growing Burden of Climate Change and Air Pollution on COPD Morbidity and Mortality - wibowo, adityo (Jurnal Kedokteran Universitas Lampung, 2025)
Chronic obstructive pulmonary disease (COPD) arises from interactions between genetic susceptibility and long-term exposure to harmful particles or gases. While smoking is known as the primary risk factor, environmental and occupational pollutants (particulate matter, biomass smoke, and diesel emissions) significantly contribute to disease development and progression. Climate change further worsens COPD by increasing ambient particulate matter, ground-level ozone, and extreme temperature events. These exposures induce oxidative stress, airway inflammation, mucus hypersecretion, and structural lung injury, leading to accelerated lung function decline and more frequent exacerbations. Extreme heat and cold further increase hospitalization and mortality in COPD patients, while indoor environmental factors driven by air-conditioning use, humidity, and poor ventilation exacerbate the symptoms. These findings highlight the growing impact of environmental pollution and climate change on COPD burden worldwide.